Fescue Hay Cost-Return Budget in Central and Eastern Kansas - Fausett, Marvin R.; Warmann, Gerald W. (My University, 1998)
This publication provides estimated cost and returns for forward farm planning for fescue hay in central and eastern Kansas.
MF2146_1998_10
Keywords: MF2146; Crops; Economics; MF